2016
DOI: 10.1186/s13054-016-1232-6
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring energy expenditure in the intensive care unit: a comparison of indirect calorimetry by E-sCOVX and Quark RMR with Deltatrac II in mechanically ventilated critically ill patients

Abstract: BackgroundIndirect calorimetry allows the determination of energy expenditure in critically ill patients by measuring oxygen consumption (VO2) and carbon dioxide production (VCO2). Recent studies have demonstrated variable performance of “breath-by-breath” instruments compared to mixing chamber technology. The aim of this study was to validate two modern devices (E-sCOVX and Quark RMR) against a reference method (Deltatrac II).MethodMeasurements of VO2/VCO2 with the test and reference devices were performed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…However, indirect calorimetry is not conducted routinely in most intensive care units (ICU) mainly due to the lack of a reliable indirect calorimeter, and manpower with appropriate expertise to conduct and analyze the results [7]. Recent studies comparing currently available calorimeters have demonstrated that the measured EE is variable from one calorimeter to another [8, 9], although they are still more consistent than the EE calculated from predictive equations [10]. …”
Section: Introductionmentioning
confidence: 99%
“…However, indirect calorimetry is not conducted routinely in most intensive care units (ICU) mainly due to the lack of a reliable indirect calorimeter, and manpower with appropriate expertise to conduct and analyze the results [7]. Recent studies comparing currently available calorimeters have demonstrated that the measured EE is variable from one calorimeter to another [8, 9], although they are still more consistent than the EE calculated from predictive equations [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Body weight, nutrition status, mid upper arm circumference and plasma albumin levels were repeated at discharge from ICU or day 15, whichever came first. In addition, measured energy expenditure (MEE) was assessed by indirect calorimetry using the E‐sCOVX (GE, Helsinki, Finland) monitor . The measurements were carried out within the first 5 days after enrolment, if a trained operator was available, and patients were excluded if they were receiving continuous renal replacement therapy, attached to extracorporeal circulation, had an intercostal catheter with an air leak, or were receiving a fraction of inspired oxygen >0.6 .…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, studies have shown that these equations sometimes give inaccurate answers despite the age, gender, or weight [80] (Table 1). On the one hand, for example, in a study performed to validate the results produced by the two methods, indirect calorimetry was found to have a ±10% degree of error for measured energy expenditure.…”
Section: Mathematical Formulas For Predicting Energy Requirementsmentioning
confidence: 99%